Rancang Bangun Robot Pemindah Barang Berbasis Mikrokontroler Untuk Monitoring Stok Gudang - Bima Jodhi Satria; Sumaryanto (Elkom : Jurnal Elektronika dan Komputer, 2020)
This study generally aims to design an information system that can handle problems in putting and sorting goods into warehouses at CV. Sekar Intan KIC Gatsu, Semarang. In terms of using the Information System, CV. Sekar Intan KIC Gatsu, Semarang. In the transfer and sort of goods in the warehouse still using a manual system when the implementation, warehouse employees must take and place the goods to the warehouse that has been determined each - each type of item, so employees must calculate the number of items when the goods take place, here various problems occur, because it requires some HR to manage the warehouse performance process at CV. Sekar Intan. To support the research, researchers used Research and Development (R & D) research methods through the microcontroller-based moving robot design simulation design stages that have been tested by experts declared valid with Valid validity levels and final product development design simulation prototypes carried out. goods transfer robot uses Arduino IDE development software that is integrated with Arduino Mega 2560, 6 pin line sensor, dc motor, motor driver, servo motor, motor driver, lcd, and has been tested in the field by General Adv. Administration and HRD as users / users and stated to be very effective. Based on the results of the research and discussion, it can be concluded that the robot design system developed can overcome the problems in the old system on the CV. Sekar Intan KIC Gatsu Semarang, so as to produce a system that can facilitate work processes and parking processes for employees to be more effective and efficient.